EPIDEMIOLOGICAL SURVEILLANCE ON DIARRHEAL DISEASES AT PASIR PANJANG PRIMARY HEALTH CARE CENTER 2025 - Wahyuni, Maria Magdalena Dwi; Weraman, Pius; Teuk, Maria; Pahul, Theresia Della; Lebangu, Yoseph Alvino Atu; Jeniut, Fransiska; Tari, Inri Welexrin (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2025)
Diarrheal disease remains a major public health concern in Kupang City, particularly in the service area of Pasir Panjang Public Health Center (PHC). Epidemiological surveillance plays a vital role in early detection and disease control. This study aims to describe the implementation of diarrheal disease surveillance at Pasir Panjang PHC. A descriptive qualitative approach involved in-depth interviews, observations, and document reviews. Informants included surveillance officers, health workers, and community health volunteers (cadres). Results showed that surveillance activities are conducted by trained personnel and supported by the Health Operational Assistance (BOK) program, which adequately funds promotive and preventive efforts. However, medicine procurement is managed by the District Health Office's Pharmacy Installation. Surveillance data are collected through reports from medical services, sub-health centers (Pustu), and cadres, with monitoring and reporting performed via the SIHEPI application. The surveillance targets all community members, especially vulnerable groups such as infants, toddlers, and the elderly. Notably, the highest incidence was found among children over five years old, potentially linked to school food hygiene, although further investigation has not been conducted. SWOT analysis revealed strengths in trained personnel and data completeness. Weaknesses include poor hygiene practices in the community (PHBS) and an increasing trend in cases. Opportunities lie in using digital media for health promotion and intersectoral collaboration to enhance surveillance efforts. These findings highlight the importance of strengthening health education and focusing on vulnerable groups to improve disease prevention and control strategies at the primary health care level.